Intersectionality as locality: children and transitional justice in Nepal - Billingsley, Krista (International journal of transitional justice, 2018)
Transitional justice policy, although predicated on an ideology of transition, often homogenizes victims and fails to respond to victims’ diverse and dynamic needs during the ‘transitional period.’ In this article, based on 14 months of ethnographic research in Nepal, I examine the perceptions and experiences of adults who were children when their fathers were killed or disappeared during the decade-long internal armed conflict between the Communist Party of Nepal-Maoists and the Nepali government. Through their varied experiences and ongoing transitions, I challenge homogeneous and fixed conceptualizations of ‘children’ and ‘the local’ and argue for greater attention to the intersectional experiences of victims and the redress of entrenched systems of domination and inequality.